A coarse-to-fine and automatic algorithm for breast diagnosis on multi-series MRI images - Xue, Hongwei; Qian, Guangwu; Wu, Xiaofen; Gao, Yan; Yang, Hongguang; Liu, Mingqian; Wang, Lei; Chen, Renfei; Wang, Peijun (Frontiers in Computer Science, 2022)
Introduction Early breast carcinomas can be effectively diagnosed and controlled. However, it demands extra work and radiologist in China often suffer from overtime working due to too many patients, even experienced ones could make mistakes after overloaded work. To improve the efficiency and reduce the rate of misdiagnosis, automatic breast diagnosis on Magnetic Resonance Imaging (MRI) images is vital yet challenging for breast disease screening and successful treatment planning. There are some obstacles that hinder the development of automatic approaches, such as class-imbalance of samples, hard mimics of lesions, etc. In this paper, we propose a coarse-to-fine algorithm to address those problems of automatic breast diagnosis on multi-series MRI images. The algorithm utilizes deep learning techniques to provide breast segmentation, tumor segmentation and tumor classification functions, thus supporting doctors' decisions in clinical practice. Methods In proposed algorithm, a DenseUNet is firstly employed to extract breast-related regions by removing irrelevant parts in the thoracic cavity. Then, by taking advantage of the attention mechanism and the focal loss, a novel network named Attention Dense UNet (ADUNet) is designed for the tumor segmentation. Particularly, the focal loss in ADUNet addresses class-imbalance and model overwhelmed problems. Finally, a customized network is developed for the tumor classification. Besides, while most approaches only consider one or two series, the proposed algorithm takes in account multiple series of MRI images. Results Extensive experiments are carried out to evaluate its performance on 435 multi-series MRI volumes from 87 patients collected from Tongji Hospital. In the dataset, all cases are with benign, malignant, or both type of tumors, the category of which covers carcinoma, fibroadenoma, cyst and abscess. The ground truths of tumors are labeled by two radiologists with 3 years of experience on breast MRI reporting by drawing contours of tumor slice by slice. ADUNet is compared with other prevalent deep-learning methods on the tumor segmentation and quantitative results, and achieves the best performance on both Case Dice Score and Global Dice Score by 0.748 and 0.801 respectively. Moreover, the customized classification network outperforms two CNN-M based models and achieves tumor-level and case-level AUC by 0.831 and 0.918 respectively. Discussion All data in this paper are collected from the same MRI device, thus it is reasonable to assume that they are from the same domain and independent identically distributed. Whether the proposed algorithm is robust enough in a multi-source case still remains an open question. Each stage of the proposed algorithm is trained separately, which makes each stage more robust and converge faster. Such training strategy considers each stage as a separate task and does not take into account the relationships between tasks.